MODELS OF ECONOMIC DEVELOPMENT TRENDS' SOCIAL ORIENTATION IN THE INNOVATIVE PROCESSES' GLOBALIZATION CONTEXT - E.I. Lazareva (Kherson State University, 2012)
In the article real ways of national welfare as the innovative economic development integrated resource' methodology and set of instruments revision are exposed, conditions, principles and factors of the national welfare new model as form of economic subjects interests coordination are conducted.